THE RELATIONSHIP OF HEADMASTERS’ SHARED LEADERSHIP AND TEACHERS’ MOTIVATION IN PRIMARY SCHOOLS - Anis Salwa Abdullah; Siti Noor Ismail, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study was carried out to examine the relationship between the headmasters’ shared leadership and the teachers’ motivation in the UPSR-excellent primary schools. Specifically, three components of shared leadership are tested, namely planning, management, and problem-solving, development and mentoring, and support and consideration. While motivation constructs are tested through eight components. A total of 120 teachers were randomly selected from three SKPM Score 4 primary schools with UPSR GPS 2015 ranging from 1.00 to 2.00 in Kelantan. The data were collected through 44 items-questionnaires using Shared Leadership Perception Survey Instrument, SLPS (Wood, 2005) and Teacher Motivation Survey Instrument, TMS (Boyle, 2014). The data were analysed using descriptive statistical analysis, t-test, ANOVA test, Pearson correlation and linear regression. The study found that shared leadership and teacher motivation in primary schools were at the high levels. In terms of the differences in motivation based on the demographic factors, there is no significant difference between male and female teachers. However, teachers' motivation based on teaching experience is significant, that teachers with 20 to 29 years of teaching experience have the highest level of motivation. This study also found that shared leadership is significantly, positively correlated to teachers' motivation. In fact, the headmasters’ shared leadership also positively and significantly influences the motivation of teachers. The K2 component is the greatest significant predictor of teachers’ motivation. The results of this study support the all the constructs, which is the shared leadership plays the important role and contributes towards improving teachers’ job motivation in primary schools. This study suggests the relationship and influence of shared leadership as a construct and its components as the significant contributors by identifying the roles and interests of each component in the shared leadership in order to increase the motivation of teachers in primary schools